Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
[tex] \: \: \: \: \: \: [/tex]
[tex] = \: \: \: \: r = 5[/tex]
Step-by-step explanation:
[tex]7 + 4(r + 3) = 9r - 6[/tex]
- distribute 4 through the parentheses
[tex]7 + 4r + 12 = 9r - 6[/tex]
- add numbers
[tex]19 + 4r = 9r - 6[/tex]
- move the variable to the left hand side and change its sign
[tex]19 + 9r = - 6[/tex]
- move the constant to the right hand side and change its sign
[tex]4r - 9 = - 6 - 19[/tex]
- collect like terms
[tex] - 5r = - 6 - 19[/tex]
- calculate the difference
[tex] - 5r = - 25[/tex]
- divide both sides of the equation by -5
[tex] = \: \: \: \: r = 5[/tex]
hope it helps
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.